2018
DOI: 10.1088/1361-6382/aaf133
|View full text |Cite
|
Sign up to set email alerts
|

The structure of BPS equations for ambi-polar microstate geometries

Abstract: Ambi-polar metrics, defined so as to allow the signature to change from +4 to −4 across hypersurfaces, are a mainstay in the construction of BPS microstate geometries. This paper elucidates the cohomology of these spaces so as to simplify greatly the construction of infinite families of fluctuating "harmonic" magnetic fluxes. It is argued that such fluxes should come from scalar, harmonic pre-potentials whose source loci are holomorphic divisors. This insight is obtained by exploring the Kähler structure of am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
(129 reference statements)
0
26
0
Order By: Relevance
“…By demonstrating that the same tools can be used in 6 dimensions we have provided another setting in which these questions might be answered. Additionally the form of the prepotentials for general (k, m, n) we constructed are richer than those known previously [27], perhaps they may shed light on some of these questions.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 95%
See 2 more Smart Citations
“…By demonstrating that the same tools can be used in 6 dimensions we have provided another setting in which these questions might be answered. Additionally the form of the prepotentials for general (k, m, n) we constructed are richer than those known previously [27], perhaps they may shed light on some of these questions.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 95%
“…In [27] it was shown that in 5-dimensions the Θ (I) can be derived from harmonic functions on the GH base known as prepotentials Φ (I) . The construction is…”
Section: Prepotentials In 5-dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These solutions are completely regular for any choice of F (see Section 3.4.1); we also do not expect the existence of CTC's for any F . The angular momenta of the solution are: 35) and the momentum charge Q P is:…”
Section: A1 Solutions With Functions Of ξmentioning
confidence: 99%
“…If we solve the zeroth layer, the remaining two layers can be written as linear differential equations on B. In practice, in most of the explicit superstratum solutions in the literature, it is assumed that the B is flat R 4 or a Gibbons-Hawking space [43,71,72], and that β is independent of v.…”
Section: The Zeroth Layermentioning
confidence: 99%